The effect of antimicrobial activity of Teucrium Polium on Oral Streptococcus Mutans: a randomized cross-over clinical trial study - Somayeh Khoramian Tusi; Ahmad Jafari; Seyed Mahmoud Amin Marashi; Salomeh Faramarzi Niknam; Malihe Farid; Mehdi Ansari (BMC, 2020)
Abstract Background The purpose of this study is to determine the effect of a mouthwash containing Teucriumpolium herb on Streptococcus mutans in mouth. Methods This study was a randomized, crossover, double-blind clinical trial, where we selected 22 volunteers (dental students) randomly and we divided them into two groups. The study had two phases. In each phase, one group acted as the intervention group, while the other one was the control group. Both the intervention and control groups were given the mouthwash with and without Teucriumpolium, respectively. S. mutans of saliva were measured before and after each phase to compare the effects of the mouthwashes. A three-week washout period was considered between the two phases. An independent two-sample t-test was utilized to compare the mean of S. mutans colonies. Additionally, we used a standard AB/BA crossover model to find the results of the treatment and the impact of carryover on the residual's biological effects. The significance level was considered 0.05 in this experiment. Results There is no significant difference observed between the two groups in the number of S. mutans before using the mouthwashes. When the mouthwash containing Teucriumpolium was used, there was a significant decrease in the number of S. mutans colonies in both phases' extract (P = 0.002). Conclusion: The results of this study indicate the mouthwash containing aqueous extract of Teucrium polium can majorly reduce the colonization of S. mutans in human saliva. Trial registration Ethical issues approved by the Ethics Committee of the Rafsanjan University of Medical Sciences with the approval number of 937/9/31, IRCT code Number of IRCT2013121815842N1 and it was approved on 06/16/2014. The study was conducted in the period of September to November 2014.